A QUALITATIVE REVIEW OF THE HEALTH AND SAFETY LEADERSHIP ROLES OF MANAGERS IN SOUTH AFRICAN CONSTRUCTION - Victor OKORIE; Fidelise Emuze; John SMALLWOOD; Jacobus VAN WYK (Journal of Construction Project Management and Innovation)
Top management in an enterprise has decisive roles to play in terms of health and safety (H&S) management. A key role in this context pertains to leadership. The study that is reported upon assessed the H&S leadership styles and behaviours of managers in South African construction. The study, which follows the phenomenological approach, obtained information that highlights H&S practices in terms of leadership styles, behaviours and attitude of managers in the construction sector. The themes of the findings show that managers play critical leadership roles in managing workers’ H&S on site; managers’ leadership styles and behaviours have considerable influence on workers’ at-risk work practices, and managers have the capability to drive team performance by creating an enabling environment for zero tolerance for H&S failures on project sites. Thus, the leadership styles and behaviours of construction managers is undoubtedly an important factor in shaping workers’ H&S behaviours in the workplace. In promoting and sustaining optimum H&S in construction, managers should endeavour to appropriate management skills that embrace transformational leadership styles, commitment to H&S, and qualities that will help them to instil and maintain a positive H&S culture.